Carotid artery intra-plaque attenuation variability using computed tomography. Issue 1 (December 2016) - Saba, Luca; Anzidei, Michele; de Cecco, Carlo; Porcu, Michele; Balestrieri, Antonella; Sanfilippo, Roberto; Francone, Marco; Mereu, Alessio; Lucatelli, Pierleone; Montisci, Roberto; Suri, Jasjit; Wintermark, Max
Abstract Background In the CT assessment of the carotid plaque, the analysis of the attenuation value is a fundamental parameter in order to classify the type of the tissue that composes the plaque. The purpose of this paper is to assess the intra-plaque attenuation variability in order to verify the potential reproducibility of HU measurements. Methods In this retrospective study, 68 consecutive patients (males 42; average age 64 ± 11 years) that underwent CT of carotid arteries were included. Exams were performed before and after administration of contrast medium and in each slice 4 different circular or elliptical ROIs (≥1 and ≤ 2 mm2 ) were traced and attenuation values were recorded. Wilcoxon and Mann-Whitney test were used to test the differences between the ROI. Results A total of 192 slices were analysed. The average value of attenuation before contrast medium was 41.591(SD 8.1) HU and 54.159 (SD 15.7) in post-contrast scan. Mann-Whitney test did not find statistically significant difference among the ROI in the pre-contrast scan whereas a statistically significant differences was found in post-contrast scan. Wilcoxon analysis showed a statistically significant difference (p value = 0.001) between pre and post-contrast attenuation. Conclusion In conclusion, results of our study suggest that ROI sampling performed in the CT dataset acquired after administration of contrast medium show significant degree of heterogeneity and a statistically significant differences compared to the baseline measurement. This effect may be driven by a different amount of contrast acquisition in some areas of the carotid artery plaque.